Standar Kecantikan dalam Karya Digital Painting - Sakina, Sauri Putri; Fitryona, Nessya (TSAQOFAH, 2025)
This study aims to visualize beauty standards through digital painting as a response to the phenomenon of low self-confidence experienced by some women regarding their bodies and identities. The artworks are intended to represent the uniqueness of women's beauty standards without insecurity, using digital painting as the chosen medium due to its effectiveness, flexibility, and wide reach among the current generation. The creative process followed the art consortium method, comprising five stages: (1) Preparation, (2) Elaboration, (3) Synthesis, (4) Concept Realization, and (5) Completion. The technique employed is digital painting creating artwork digitally using hardware and software, specifically utilizing the Procreate application on an iPad. The final outcome consists of ten artworks, each measuring 100 x 100 cm, titled: (1) Goresan Tubuh, (2) Albino, (3) Topeng, (4) Gadis Kecil, (5) Cerminan Diri, (6) Tanda Lahir, (7) Berbeda, (8) Tanpa Batas, (9) Harmonis, and (10) Pejuang. Each piece conveys a visual narrative reflecting diversity and self-acceptance as a critique of the homogenization of beauty standards. The creation of these works is expected to encourage women to build self-worth, embrace imperfections, and love themselves wholly.